GAMBARAN HASIL CT SCAN KEPALA NON KONTRAS PADA PASIEN STROKE DI BAGIAN INSTALASI RADIOLOGI RUMAH SAKIT DAERAH KOTA TIDORE KEPULAUAN TAHUN 2018 - safwan pratama Bachmid; dewi darmayanti; Liasari Armaijn (Kieraha Medical Journal, 2020)
ABSTRACTBackground: Stroke is defined as a syndrome that has characteristic neurological signs and symptoms that develops rapidly, interferes with cerebral function, or causes death without any cause other than vascular origin. Stroke is clinically divided into two namely non-hemorrhagic stroke and hemorrhagic stroke. Objective: The purpose of this study was to determine the description of the results of non-contrast CT head scans based on the characteristics of stroke patients in Tidore Islands Regional Hospital. Methode: This research is a retrospective descriptive study with sources from secondary data on CT scan radiology and medical records at the City Hospital of Tidore during the January-December 2018 period. Results: From the CT scan results, there were 89 stroke patients, of which 72 patients were diagnosed with ischemic stroke (80.9%) and 17 patients were diagnosed with hemorrhagic stroke (19.1%). From this data it is known that more men (57.3) than women (42.6%). The largest age group that suffered a stroke was in the age range of 45-54, as many as 28 patients (31.4%) and the age group 25-34 were the age group that suffered the least stroke by 2 patients (2.24%). The highest monthly distribution of cases occurred in January with 13 patients (14.6%). The most CT picture in stroke patients is hypodense as many as 64 patients (71.9%). The highest risk factor that can be changed is hypertension (25.08%) followed by dyslipidemia (14.60%). Conclusion : After CT head examination, most patients are ischemic stroke patients with hypodense lesions. Keywords:  Head CT scan, Ischemic Stroke, Hemorrhagic Stroke,  RSD Tidore Island